Bibliometric Analysis of Polyethersulfone (PES) Membrane Research Development (2012-2022) Using Publish or Perish and VOSviewer - Silvia Widiyanti; Asep Bayu Dani Nandiyanto (Jurnal Teknologi Riset Terapan, 2025)
Purpose: Polyethersulfone (PES) membranes are widely used in filtration and gas separation due to their strong thermal, mechanical, and chemical stability. However, no comprehensive bibliometric mapping of PES membrane research has been conducted. This study aims to analyze publication trends, research quality, influential works, and thematic evolution in PES membrane literature from 2012 to 2022.Methodology: Bibliometric data were retrieved from Google Scholar using Publish or Perish with keywords related to Chemistry, Particle, PES, and Membrane, covering 1,000 articles (2012–2022). VOSviewer was used for analysis through network visualization (co-word clustering), overlay visualization (temporal trends), and density visualization (research intensity). A minimum co-occurrence threshold of five keywords produced 170 significant terms.Results: Publications increased from 55 in 2012 to 123 in 2020, averaging about 90 papers annually. Of 1,000 articles, 77.8% were published in Q1 journals, with Elsevier contributing 61.4%. Eight thematic clusters were identified, highlighting mixed matrix membranes and MOF-based membranes as dominant research directions.Conclusions: PES membrane research shows strong growth and high publication quality, evolving toward advanced mixed matrix and MOF/COF-based membrane technologies.Limitations: The dataset is limited to Google Scholar, partial 2022 coverage, and keyword constraints that may exclude relevant studies.Contributions: This study provides the first bibliometric baseline for PES membrane research, mapping trends, quality distribution, and thematic evolution to guide future research directions.